Floristic analysis of a high-speed railway embankment in a Mediterranean landscape - Filibeck, Goffredo; Cornelini, Paolo; Petrella, Paolo (Acta Botanica Croatica, 2012)
We analyzed the floristic composition of a 4.5 km-long segment of a high-speed railway in Lazio, central Italy, which travels on an artificial embankment through an intensively-farmed landscape. In total, 287 vascular plant species were recorded. The life-form distribution was found to be similar to that of the regional species pool, with high percentages of therophytes (38%) and phanerophytes (13%). In the chorological spectrum the Mediterranean floristic element prevailed (44%), while alien species were 8% of the flora. The phytosociological spectrum showed a high diversity of characteristic species from the class Stellarietea mediae or its subordinate syntaxa (26%), and in particular from the order Thero-Brometalia (Mediterranean, sub-nitrophilous annual communities). Species from forest syntaxa had a relatively high diversity (9%). These results suggest that the ecological filtering provided by the Mediterranean regional climate controlled species assemblage even in a completely artificial habitat, preventing floristic homogenization: the flora of the studied railway section is only partially »ruderalized«, while it keeps strong links with the regional (semi-) natural plant communities. However, in contrast to what is observed in central and north Europe, the railway sides studied in the present paper do not seem to represent a refugial habitat for rare species from grassland communities, mainly because in Italy semi-natural dry grasslands are still widely represented.